Ofensiva do capital e desmobilização das forças do trabalho: as estratégias gerenciais burguesas para a desarticulação das classes trabalhadoras - Serafim, Rodrigo Albuquerque (2012)
The problematic that gives shape to this research is the question of the historical process of demobilization of the movement of the working classes in your accented contemporary moment. Their object of study, however, and that it particularizes, it relates to a portion this problematic; it relates to set of determinations that comprise a broader set of determinations of this historical process: it is a set of determinations forged and mediated by bourgeois strategies of management for the conformation of the circumstances necessary for the domination and for the conduct of labor force on operations in work processes for the production of surplus value. What we investigated are, because, the strategies of disarticulation that the bourgeoisie utilizes, under the mantle of subsidies conceptual and interventive of its management of work processes and the sieve of class struggles, to obstruct the union of workers; hamper the movements proletarians. Managerial strategies that intentionally or unintentionally, instill in the social relations of production means to produce and reproduce, activate and reactivate conditions of incitement of individualism and competition between the workers themselves. We shall see, thus, by analyzing means, centrally, from some of the fundamentals of disarticulation in the managerial strategies bourgeois and some of the fundamental strategies of management bourgeois hegemonized with the restructuring productive of 1970, that the disarticulation, and also the demobilization, is a concrete condition, is an objective condition, that is beyond a question that can be "solved" only by enlightenment cognitive, only by formation criticism intellectual. In everyday of the work spaces permeated by managerial strategies bourgeois there elements, then, operating as a material force putting difficulties important for the articulation of the workers, the solidarity of the proletariat; elements that constitute obstacle significant to an awareness of class and belonging; elements act in favor of the atomization of the worker - even if engenders, in the same process, as a contradiction, potentiality of resistance and fight the forces of labor